Status of amphistomiasis in cattle at Joypurhat district of Bangladesh - Azam, MG; Begum, N; Ali, MH (Bangladesh Journal of Animal Science, 2012)
In Bangladesh, livestock are affected by different types of helminth parasites of which amphistomiasis in cattle is known to be widespread and death may occur in some cases. An experiment was conducted to investigate the status of amphistomiasis in cattle, 64 visceral and 360 faecal samples were collected from different areas of Joypurhat district during May 2009 to April 2010. Faecal and visceral sample examinations showed 70.8% and 90.6% infection with amphistomiasis, respectively. It was observed that age had a significant influence on the prevalence of amphistomiasis. In faecal samples, higher prevalence was observed in adult cattle (84.9%) followed by the young (77.3%) and lowest in calf (16.7%). On the basis of examination of visceral sample, females (93.8%) were found to be significantly more infected than male (89.9%) with the amphistome. The prevalence of amphistomiasis in crossbred cattle (90.9% in faeces and 93.9% in viscera) was significantly higher than indigenous cattle (62.2% in faeces and 89.8% in viscera). The calculated odds ratio implied that the crossbred cattle were 1.6 times (viscera) and 4.2 times (faeces) more affected than indigenous cattle. Prevalence rate was higher in rainy season (79.2% in faeces and 95.5% in viscera) followed by winter (68.3% in faeces and 90% in viscera) and summer (65% in faeces and 86.4% in viscera) season, but with no significant effect on the prevalence of amphistomiasis. Feeding habit had significant effect on the prevalence of amphistomiasis. Pasture grazing cattle (82.5%) were more (2.9 times) affected than stall feeding cattle (59%). DOI: http://dx.doi.org/10.3329/bjas.v40i1-2.10788 Bang. J. Anim. Sci. 2011. 40 (1-2): 34-39